In Memoriam: The Pioneering Contributions of Martin K. Starr, Editor-in-Chief of Management Science (1967–1982) - Loch, Christoph; Singhal, Kalyan; Tang, Christopher (Management Science, 2025)
Martin K. Starr, aged 97, passed away January 25, 2025. During his 15-year tenure as editor-in-chief of Management Science, he became the longest serving editor of any INFORMS journal. During this period, he published dozens of books and more than 100 articles. Starr made significant contributions to delineating the domain of modern operations and supply chain management, building a framework for system integration, modular design and production, and high-risk systems. This essay intends to underscore Martin Starr’s contributions to the field of management science, particularly emphasizing the crucial connection between theoretical analysis and practical applications in management.